Colletotrichum Disease of Cocoa (Theobroma Cacao L.) and its Control - Yee, Ming Fatt (1991)
Isolation of disease pathogen from infected cocoa leaves and pods associated with leaf spot and pod rot disease yielded Colletotrichum gloeosporioides. No distinct differences in cultural and morphological characteristics were noted from the various isolates. Further investigation by polyacrylamide vertical gel electrophoresis indicated that protein, esterase and peroxidase patterns were unable to differentiate strain gloeosporioides. variation within C. The fungus was found to grow and sporulate well at 30°C. Cocoa Leaf Extract Agar (CLEA) was the best medium for mycelial growth while Potato Dextrose Agar (PDA) appeared to favour sporulation. Better mycelial growth was also achieved on substrates of neutral condition while extreme alkaline condition induces sporulation. Both cocoa leaves and injured pods were liable to infection by C. gloeosporioides. Three-week old cocoa seedlings and cherelles were noted as the most susceptible stage. The development of Colletotrichum leaf spot disease invariably involved three phases of activity viz., prepenetration phase which involved spore germination and formation of appressoria, penetration phase involving intercellular and intracellular hyphal penetration and postpenetration phase resulting in disintegration of cells and the formation of acervuli.